2017
DOI: 10.1158/0008-5472.can-16-1693
|View full text |Cite|
|
Sign up to set email alerts
|

Wnt5a Drives an Invasive Phenotype in Human Glioblastoma Stem-like Cells

Abstract: Brain invasion by glioblastoma determines prognosis, recurrence, and lethality in patients, but no master factor coordinating the invasive properties of glioblastoma has been identified. Here we report evidence favoring such a role for the noncanonical WNT family member Wnt5a. We found the most invasive gliomas to be characterized by Wnt5a overexpression, which correlated with poor prognosis and also discriminated infiltrating mesenchymal glioblastoma from poorly motile proneural and classical glioblastoma. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
103
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(110 citation statements)
references
References 49 publications
6
103
0
Order By: Relevance
“…In this study, we used GSC cultures that were previously extensively characterized for their stem-like capacity (22,48). A recent publication proposed a critical role of the apelin/APLNR signaling pathway in GSC maintenance (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we used GSC cultures that were previously extensively characterized for their stem-like capacity (22,48). A recent publication proposed a critical role of the apelin/APLNR signaling pathway in GSC maintenance (49).…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture GBM stem-like cell (GSC) were derived from human glioblastoma biopsies [as previously reported for NCH644 and NCH588J (20); GBM10, GBM13 and GBM14 (21); and GBM5av to 10av (22)] and were maintained under stem cell cultivation conditions in DMEM-F12 (catalog no. 11320-074) supple-mented with 1 Â B27 (catalog no.…”
Section: Methodsmentioning
confidence: 99%
“…GBM is characterized by complex tissue heterogeneity, in which there is a class of stem cell-like tumor-initiating cells, called GSCs, which have the ability to self-renew, grow continuously and differentiate into multiple neural cell types [34][35][36]. Further studies found that GSCs are key factors leading to the occurrence, recurrence, treatment tolerance and poor prognosis of glioma [35,[37][38][39][40]. We successfully propagated eight human GSC lines with four different molecular subtypes and found the highest PSAP expression and secretion in mesenchymal GSCs, as determined by western blotting and ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…This study explores TSPO and LAT1 expression in human and murine GBM tissue from different GBM subtypes (Table A1). GBM stem-like cells (GSCs) were derived from human GBM of different genetic subtypes, namely proneural [20,21] and classical [22], and were cultured as spheroids until xenografting them into immunodeficient mouse brains to produce GBM. Mouse transgenic GSCs used to model genetic GBM subtypes were derived from transgenic neural precursor cells that were additionally transduced to carry typical driver mutations for proneural (p53 KO PDGFB) or classical (cdkn2a KO EGFRvIII) GBM subtypes [23,24] and were kept under stem cell-like conditions until orthotopic implantation into immunocompetent mice.…”
Section: Introductionmentioning
confidence: 99%